CLEC5A Mediates Macrophage Function and COPD Pathologies() - Wortham, Brian W. (J Immunol, 2016)
Chronic Obstructive Pulmonary Disease (COPD) is a devastating disease with no effective therapies. We investigated the role of the C-type lectin receptor, CLEC5A, in macrophage activation and pulmonary pathogenesis in a mouse model of COPD. We demonstrate that CLEC5A is expressed on alveolar macrophages in mice exposed long-term to cigarette smoke (CS) and in human smokers. We also show that CLEC5A-mediated activation of macrophages enhanced cytokine elaboration alone, and in combination with LPS or GM-CSF in CS-exposed mice. Furthermore, using Clec5a-deficient mice, we demonstrate that CS-induced macrophage responsiveness is mediated by CLEC5A and CLEC5A is required for the development of inflammation, proinflammatory cytokine expression and airspace enlargement. These findings suggest a novel mechanism that promotes airway inflammation and pathologies in response to CS exposure and identifies CLEC5A as a novel target for the therapeutic control of COPD pathogenesis.